(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: The study aimed to describe some epidemiological and histopathological characteristics of lung cancer in Hanoi from 2015 to 2019. Methods: Retrospective study. Data were recorded from 30 hospitals in Hanoi according to the principles of organization of population cancer registration recommended by the International Agency for Research on Cancer (IARC) from January 1, 2015 to December 31, 2019. The total number of disease stages (n=966) and histopathology (n=1351) were recorded. Results: The disease was mainly detected at the late stage (71.2% were stage IV and 20.3% were stage III). The rate of stage IV lung cancer was highest in both urban and suburban areas. However, the urban area (74.9 %) was higher than the suburban area (69.0%). From stage 0 to III, the suburbs were higher than the urban area. According to histopathology results, adenocarcinoma had the highest rate (60.5%) and was higher in females than in males (79.4% vs. 53.7%). Small and squamous cell lung cancer was more common among males (11.6% and 14.5%) than in females (1.1% and 5.4%). Conclusions: Lung cancer was found late, so the mortality rate was high. Therefore, it was necessary to strengthen screening and early detection of lung cancer in people at risk to help choose appropriate interventions to inhibit cellular activities and improve the patient’s quality of life.